Influence of morphology and strength on front crawl swimming speed in junior and youth age-group swimmers - Strzala, M.; Stanula, A.; Krezalek, P.; Ostrowski, A.; Kaca, M.; Glab, G. (The Journal of Strength and Conditioning Research, 2019)
This study, conducted in 2 male age groups, was aimed at analyzing the influence of body properties, dry-land strength and swimming strength on 50-m crawl (VCrawl). We examined 2 competitive groups, Youth (20.6 ± 1.05) and Junior (17.3 ± 0.59), based on (a) body mass (BM) and lean body mass (LBM), body height (BH) and total body length (TBL), and arm span (AS); (b) countermovement jump (CMJ) and maximum isometric strength of elbow and knee joints; and (c) tethered crawl strength. We hypothesized that a higher relationship of strength indices in younger swimmers in VCrawl and tethered swimming would be a better sprint performance predictor. The Junior group revealed a significant relationship between somatic traits (BM r = 0.63; BH r = 0.55; TBL r = 0.58; AS r = 0.52 with p 0.05 LBM r = 0.78; with p < 0.01) and VCrawl, whereas such interplay was not found in the Youth group. General dry-land strength indices CMJ (cm), CMJ (J) or isometric strength of knee joint muscle flexors and extensors (r = 0.57; r = 0.69; r = 0.56; r = 0.57, respectively) also significantly correlated with VCrawl only in the Junior group. The Junior group's tethered swimming strength had a higher but not a significant relationship with VCrawl. The Youth group instead achieved significantly higher VCrawl and stroke rate (SR). The SR revealed (r = 0.41, p = 0.014) a relationship with VCrawl only after the combination of both groups. This study demonstrates a better strength relationship with VCrawl in the younger Junior group. In the future, the evaluation of sprint swimming aptitudes, besides on the basis of somatic traits and properties of dry-land or water strength measurement, should be complemented by measurements of real sprint swimming technique parameters.